Virtual care expansion in the Veterans Health Administration during the COVID-19 pandemic: clinical services and patient characteristics associated with utilization. (30th October 2020) - Ferguson, Jacqueline M; Jacobs, Josephine; Yefimova, Maria; Greene, Liberty; Heyworth, Leonie; Zulman, Donna M
Abstract: Objectives: To describe the shift from in-person to virtual care within Veterans Affairs (VA) during the early phase of the COVID-19 pandemic and to identify at-risk patient populations who require greater resources to overcome access barriers to virtual care. Materials and Methods: Outpatient encounters (N = 42 916 349) were categorized by care type (eg, primary, mental health, etc) and delivery method (eg, in-person, video). For 5 400 878 Veterans, we used generalized linear models to identify patient sociodemographic and clinical characteristics associated with: 1) use of virtual (phone or video) care versus no virtual care and 2) use of video care versus no video care between March 11, 2020 and June 6, 2020. Results: By June, 58% of VA care was provided virtually compared to only 14% prior. Patients with lower income, higher disability, and more chronic conditions were more likely to receive virtual care during the pandemic. Yet, Veterans aged 45–64 and 65+ were less likely to use video care compared to those aged 18–44 (aRR 0.80 [95% confidence interval (CI) 0.79, 0.82] and 0.50 [95% CI 0.48, 0.52], respectively). Rural and homeless Veterans were 12% and 11% less likely to use video care compared to urban (0.88 [95% CI 0.86, 0.90]) and nonhomeless Veterans (0.89 [95% CI 0.86, 0.92]). Discussion: Veterans with high clinical or social need had higher likelihood of virtual service use early in the COVID-19 pandemic; however, older, homeless, and rural Veterans were less likely to have video visits, raising concerns for access barriers. Conclusions and Relevance: While virtual care may expand access, access barriers must be addressed to avoid exacerbating disparities.